Ocular flutter as presenting manifestation of pediatric MOG antibody–associated demyelination: A case report. (January 2019) - Breza, Marianthi; Smyrni, Nikoletta; Koutsis, Georgios; Anagnostou, Evangelos; Tzartos, John; Velonakis, Georgios; Kokkinis, Constantinos; Kilindireas, Constantinos; Papavasiliou, Antigone; Kotsalis, Charalambos
A 13-year-old girl presented with a 5-day history of oscillopsia. On examination, ocular flutter and mild cerebellar signs were found. Brain magnetic resonance imaging (MRI) revealed four periventricular and subcortical non-enhancing lesions. Cerebrospinal fluid (CSF) oligoclonal bands were negative. Neuroblastoma or other malignancies were not found. She responded well to a corticosteroid–intravenous immunoglobulin (IVIG) combination and remained symptom-free for 3 years until presenting again with isolated ocular flutter. Brain MRI at this time remained atypical for classic multiple sclerosis (MS) with a predominance of juxtacortical demyelinating lesions. CSF was positive for oligoclonal bands. Serum myelin oligodendrocyte glycoprotein (MOG) antibodies were present. Ocular flutter can be the presenting feature of MOG antibody–associated pediatric demyelination.